P2p Lending: Complement or Substitute to Small Bank - Dewi Tamara; Asnan Furinto; Andreas Hakim; Djury Santosa (Syntax Idea, 2021)
Rapid P2P lending growth in Indonesia is expected to bring new opportunities as well as risk to the traditional financial sector. Meanwhile, covid-19 pandemic have also brought many changes to the financial landscapes. In this current pandemic situations, not many studies have been conducted about the impact of P2P especially on small bank loans, which is the type of bank that will be the first to feel the disruption in performance, if any, as well as comparing the impact between pre pandemic and during the pandemic period. Thus, this paper aims to analyze and compare the effect of P2P lending growth on the growth of small bank loans, which consists of 56 banks as of June 2021, both before (January 2019-March 2020) and during the pandemic (April 2020-June 2021). We believe focusing the research on small banks is important because these are the incumbent players in the financial sector that are expected to be the most impacted by the arrival of the P2P lending business and the pandemic situation. This research used the quantitative approach. The analysis was carried out in stages using monthly secondary panel data obtained from OJK and BPS with multiple regression analysis. The variables we used are small bank loan growth as the dependent variable, and P2P loan growth, inflation, and money supply as the dependent variables. First we analyzed the data before the pandemic, then we analyzed after the pandemic data and compared both results. Results of this study showed that P2P lending did not have a significant impact on small bank’s ability to disburse loans before the pandemic. However, our subsequent analysis regarding data during the pandemic showed that P2P lending has a significant positive impact on small bank loans growth, and gave evidence of P2P complementary effect to small banks. Both results suggest that initially before the pandemic P2P main customer is the unbanked population that cannot have access to banks, then when the pandemic occurs, borrowers that have access to small banks also consider to use P2P as their additional financing source